Dugaan Pelanggaran Perilaku Anti Persaingan Perjanjian Tertutup Dari Industri Dalam Negeri (IDN) Pemohon Safeguards Measures - Anggraini, Shela Dwi; Hidayah, Lili Naili; Raffles, Raffles (Wajah Hukum, 2025)
In this study, the author analyzes the alleged violations committed by the Domestic Industry (IDN) Applicant for Safeguards Measures in the KPPI report document, namely the closed tying in agreement. The problem formulation in this research is how the case study of the IDN's application for Safeguards Measures at KPPI is tested with the analysis of Law No. 5 of 1999, and what preventive measures are taken by IDN. The purpose of this research is to analyze the alleged violation of tying in agreement committed by IDN, the applicant for the Safeguards Measure. The approaches used in this research include conceptual, case, legislative, and empirical legal approaches. The result of this research indicates that the IDN applicant for Safeguards Measures is suspected of violating Article 15, paragraph 2 of Law Number 5 of 1999 by using the Per se illegal and rule of reason approaches. With the evidence from the study conducted by the KPPU together with the relevant parties of the Safeguards Measures applicants. The alleged violations committed by IDN resulted in anti-competitive behavior and hindered business competition. The Safeguards Measures policy can be obtained by IDN that does not violate the laws and regulations. Law enforcement serves as a preventive measure against violations of regulations in this study, with the compliance program initiated by the KPPU as an effort to prevent violations of Law Number 5 of 1999.